Boy meets boy - Levithan, David (Ember, 2013)
Love is never easy. Especially if you're Paul. He's a sophomore at a high school like no other, and these are his friends: Infinite Darlene, the homecoming queen and star quarterback. Joni, Paul's best friend who may not be his best friend anymore. Tony, his other best friend, who can't leave the house unless his parents think he's going on a date...with a girl. Kyle, the ex-boyfriend who won't go away. Rip, the school bookie, who sets the odds... and Noah, the boy. The one who changes everything.